Stimulation of water and calcium dynamics in astrocytes with pulsed infrared light. Issue 5 (23rd March 2020) - Borrachero‐Conejo, Ana I.; Adams, Wilson R.; Saracino, Emanuela; Mola, Maria Grazia; Wang, Manqing; Posati, Tamara; Formaggio, Francesco; De Bellis, Manuela; Frigeri, Antonio; Caprini, Marco; Hutchinson, Mark R.; Muccini, Michele; et al.
Abstract: Astrocytes are non‐neuronal cells that govern the homeostatic regulation of the brain through ions and water transport, and Ca 2+ ‐mediated signaling. As they are tightly integrated into neural networks, label‐free tools that can modulate cell function are needed to evaluate the role of astrocytes in brain physiology and dysfunction. Using live‐cell fluorescence imaging, pharmacology, electrophysiology, and genetic manipulation, we show that pulsed infrared light can modulate astrocyte function through changes in intracellular Ca 2+ and water dynamics, providing unique mechanistic insight into the effect of pulsed infrared laser light on astroglial cells. Water transport is activated and, IP3 R, TRPA1, TRPV4, and Aquaporin‐4 are all involved in shaping the dynamics of infrared pulse‐evoked intracellular calcium signal. These results demonstrate that astrocyte function can be modulated with infrared light. We expect that targeted control over calcium dynamics and water transport will help to study the crucial role of astrocytes in edema, ischemia, glioma progression, stroke, and epilepsy.